Ex-vivo Placental Lipid Metabolism of Normal Weight, Overweight and Diabetic Women: A Preliminary Study (Journal of Environmental Bioremediation and Toxicology, 2021)
Obesity and diabetes mellitus are documented major risk factors for maternal and fetal health complications. Maternal lipid metabolism is greatly changed when pregnancy is complicated with obesity and diabetes mellitus. The effects of maternal obesity on placental lipid metabolism are not fully understood and thereby needs to be elucidated. Our objective is to study the lipid metabolism in the placenta of normal weight, overweight/obese and diabetic women, and to assess placental, maternal and cord serum triglycerides (TG). The term placentae, maternal and cord blood were collected from three (3) normal weight, three (3) overweight/obese and two (2) diabetic women during elective caesarean sections. The total lipid content of the placenta was measured using the Folch method. Lipolysis assay was carried out in placental tissue explant using an optimized method. Triglyceride levels of placental tissue, maternal, and cord serum were measured using a commercial reagent kit. The Placental total lipid (mg/500mg placental tissue) deposition was highest in the overweight (35.7Â±0.5), followed by diabetic (30.7Â±3.4) women, while both these groups had significantly higher (P
Keywords: placental tissue explants; total lipid; lipolysis; triglycerides; maternal obesity